A novel mathematical model for Integration of Production Planning and Maintenance Scheduling - Rastgar, Iman; Rezaeian, Javad; Mahdavi, Iraj; Fattahi, Parviz (International Journal of Industrial Engineering and Management, 2023)
The integration of production and scheduling of a shop floor, which has recently received attention both in practice and theory, is critical to achieving the optimal operational performance of production planning. The main novelty of this paper is the integration of the strategic decision with the tactical-operational decision to propose a new integrated production and scheduling mathematical model. In small instances, the model is solved by an epsilonconstraint method. To address the high complexity of large-scale problems, this study innovates new hybrid optimization algorithms. In this regard, MOPSO, NSGA-II, MOHS, and IMOHS are considered the optimization tools to solve the proposed model. To confirm their efficiency, an extensive comparison with individual algorithms is carried out by different multi-objective optimization metrics. Finally, some sensitivity analyses are performed to discuss some practical implications. The results show the advantages and effectiveness of the IMOHS in reporting the optimal Pareto for the proposed model compared to the other three algorithms. Article history: Received (October 9, 2022); Revised (April 14, 2023); Accepted (April 26, 2023); Published online (May 10, 2023)